2017
DOI: 10.1515/arls-2017-0013
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of Melissa officinalis L., Mentha piperita L., Origanum vulgare L. and Malva mauritiana against Bacterial Microflora Isolated from Fish

Abstract: The aim of the present study was to detect the antibacterial activity of medicinal plants against fish microflora. A total of 4 ethanolic extracts of 6 plant species were collected from local environments of Slovakia and screened for antibacterial activity against bacterial microflora. Extracts of Melissa officinalis L., Mentha piperita L., Origanum vulgare L. and Malva mauritiana were used. Bacterial strains were isolated from common bleak (Alburnus alburnus) and common rudd (Scardinius erythrophthalmus) of L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Indeed, Ehsani et al [ 43 ] reported the possible appropriate application of Melissa officinalis EO in the food industry, due to its antioxidant and antibacterial properties against four important food-borne bacteria ( Salmonella typhimurium , Escherichia coli , Listeria monocytogenes , and Staphylococcus aureus ). Furthermore, a strong antimicrobial activity of Melissa officinalis EO against bacterial microflora isolated from fish was also described [ 44 ]. However, in this study, we also obtained good results for Leptospermum scoparium , Satureja montana , and Cymbopogon citratus EOs against all selected S. pseudintermedius strains.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Ehsani et al [ 43 ] reported the possible appropriate application of Melissa officinalis EO in the food industry, due to its antioxidant and antibacterial properties against four important food-borne bacteria ( Salmonella typhimurium , Escherichia coli , Listeria monocytogenes , and Staphylococcus aureus ). Furthermore, a strong antimicrobial activity of Melissa officinalis EO against bacterial microflora isolated from fish was also described [ 44 ]. However, in this study, we also obtained good results for Leptospermum scoparium , Satureja montana , and Cymbopogon citratus EOs against all selected S. pseudintermedius strains.…”
Section: Discussionmentioning
confidence: 99%
“…These isolates were chosen from a total of 1,002 LAB analyzed in a previous study (Margalho, 2020), due to their high performance in technological tests: extracellular lipolytic and proteolytic enzyme production (Sahraoui et al, 2015), growth in the presence of NaCl, bile salts, and low pH values (Guo et al, 2010). The identification of strains was performed using the MALDI-TOF MS Biotyper (Bruker Daltonik GmbH, Bremen, Germany), according to Klūga et al (2017). All isolates were kept frozen (−80°C) in de Man, Rogosa, and Sharpe (MRS) broth (Merck, Darmstadt, Germany) added with 20% (vol/vol) of glycerol (Sigma, St. Louis, MO).…”
Section: Lab Isolatesmentioning
confidence: 99%
“…The authors speculated that mint essential oils’ antibacterial action depends not only on essential oil concentration, but also on food product (type, pH, storage temperature) and type of spoilage microbiota. Klūga et al [ 198 ], reported that M. × piperita leaf extract protected fish from spoilage. Also, mint extract treatment suppressed total Enterobacteriaceae and Pseudomonas spp.…”
Section: Shelf-life Prolongationmentioning
confidence: 99%